Dosimetric impact of aperture‐restricted VMAT on heart dose in breast cancer treated with regional nodal irradiation - Anh Hong Duong; Mandeep Kaur; Sunil W. Dutta; Tsegawbizu Gebru; Jacob Adams; Mark Cicchino; Reshma Jagsi; Sheela Hanasoge; Oluwatosin Kayode; Eduard Schreibmann; Hania Al‐Hallaq; Matthew Thomas; et al. (Journal of Applied Clinical Medical Physics, 2026)
Abstract Background Volumetric modulated arc therapy (VMAT) is increasingly used for breast and chest wall (CW) treatment with regional nodal irradiation (RNI) because of its ability to sculpt dose around complex target volumes. However, VMAT can increase low‐dose radiation to surrounding normal tissues and particularly increase cardiac dose. Purpose To evaluate the dosimetric impact of a strategic aperture‐restricted beam geometry, compared with traditional open‐field geometry in VMAT planning for comprehensive left‐sided breast/CW irradiation with RNI across three linac platforms. The impact of convergence mode settings was also investigated. Methods Fourteen patients with left‐sided breast/CW irradiation including comprehensive RNI were retrospectively included. For each patient, a patient‐specific optimization template with a prescription of 40.05 Gy in 15 fractions was applied across three linac platforms (Varian TrueBeam, Varian Halcyon, and Elekta Versa HD), using two beam geometries: an open‐field approach, in which field sizes fully encompassed the targets, and an aperture‐restricted approach, in which the deep field border was limited to reduce beam entry to the heart and ipsilateral lung. Jaw tracking was enabled on the TrueBeam and Versa HD linacs. Each plan was also evaluated across three convergence modes (“Off,” “On,” and “Extended”), resulting in 18 plans per patient. All plans were normalized such that 95% of the breast/CW planning target volume received 95% of the prescription dose. Dosimetric endpoints include mean heart dose, ipsilateral lung V17Gy, contralateral lung V4Gy, and contralateral breast/CW V5Gy. Total monitor units (MUs) were evaluated, and patient‐specific quality assurance (PSQA) was performed for the three highest‐MU plans on each linac platform. Paired tests were used to compare across plans. Results Target coverage was maintained after plan normalization. Aperture‐restricted VMAT significantly reduced mean heart dose compared with open‐field geometry across all linac platforms and convergence modes. The proportion of plans exceeding mean heart dose of 4 Gy was substantially lower with aperture‐restricted geometry compared to open‐field plans (2.4% vs 26.2%). The largest reduction in mean heart dose was observed with the “Off” convergence mode, decreasing from 4.20 to 2.71 Gy on TrueBeam, 3.32 to 2.58 Gy on Halcyon, and 3.97 to 2.84 Gy on Versa HD. Ipsilateral lung V17Gy was also significantly reduced with aperture‐restricted beam geometry, with only one exception on Halcyon using the “Extended” mode. No significant differences were observed in contralateral lung V4Gy, although contralateral breast/CW V5Gy increased significantly, representing a dosimetric tradeoff associated with the aperture‐restricted geometry. Aperture‐restricted beam geometry significantly increased MUs; however, PSQA passed for the three highest‐MU plans on each linac platform according to our clinical criteria. Additionally, more extensive convergence modes were associated with improved plan quality, particularly in reducing hotspot dose (D0.1cc) and enhancing cardiac and ipsilateral lung sparing. Conclusions Aperture‐restricted beam geometry significantly reduced mean heart dose and ipsilateral lung dose while maintaining target coverage across all three linac platforms, supporting its potential clinical value in VMAT planning for comprehensive left‐sided breast/CW irradiation with RNI, albeit with increased contralateral breast/CW dose. When combined with a more extensive convergence mode, overall plan quality was further improved.